Evaluation of the Performance of Perumda Air Minum Tirta Khayangan Sungai Penuh City Using the Balanced Scorecard Method for 2019-2022 - Muhammad Fajran; Iskandar Sam; Salman Jumaili (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to examine and describe how the Regional Public Company (Perumda) Drinking water, Tirta Khayangan, Sungai Penuh City uses the Balanced Scorecard with the perspectives of finance, customers, internal business processes, growth and learning. Customers and employees of Perumda Air Minum Tirta Khayangan and the company's financial statements for 2019, 2020, 2021 and 2022 are used as the population of this study. The simple random sampling technique with the slovin formula in this study obtained a total sample of 100 customer respondents and 101 respondents from the Perumda Air Minum Tirta Khayangan City of Sungai Penuh. Descriptive research with a quantitative focus was used for this study.